Analyzing Relative Efficiency of Indian Comm·ercial Banks Using DEA Approach - Aggarwal , Monika (Gyan Management Journal, 2008)
Indian banking industry has seen a number of phases till now. It started from privatization of banks, shifted to nationalization and then again focus shifted to privatization. Now after the successful implementation of financial sector reforms-I and II, the banking sector is ready for the phase of consolidation. In the present move where the focus is on competition, consolidation and efficiency the present study attempts to measure the relative efficiency of Indian Commercial banks. Data of 82 scheduled commercial banks comprising of 8 banks from State bank group, 19 banks from nationalized group, 26 banks from private sector bank group and 29 foreign banks were studied using Data envelopment analysis technique of measuring relative productivity. It was found that majority of the banks were inefficient.